Leveraging Size: Congressional Simulations in a Large Lecture Course. (22nd December 2021) - Battaglini, Charles; Gomez, Jose; Kim, Ki Young; LaBelle, James; Libonate, Casey; McClellan, Oliver A.; Roman, Carly; Rubio, Julia Maria; Miller, Michael G.
Abstract: The large introductory classes at many universities present a particular challenge for instructors wishing to guarantee participation opportunities for their students. Yet, large courses can actually afford advantages for instructors looking to replicate many features of the U.S. Congress. We describe two separate Congressional simulations in an Introduction to American Politics class of more than 300 students, including simulated committee hearings and markup, as well as a floor debate. We demonstrate how simulations can be scaled to classes of almost any size, regardless of whether they include teaching assistants.